Risk factors and knowledge of the elderly people about chronic kidney disease - Delgado, Millena Freire; Lisboa, Isabel Neves Duarte; Fernandes, Maria Isabel da Conceição Dias; Carino, Ana Carolina Costa; Fernandes, Renata Marinho; Lira, Ana Luisa Brandão de Carvalho (Rev Rene, 2017)
Objective: to analyze the relationship between the risk factors and the elderly people knowledge about chronic kidney disease. Methods: this study is a cross-sectional research with 100 elderly enrolled in basic units, using asemi-structured interview. Data were analyzed using descriptive and inferential statistics. Results: most elderly people had adequate knowledge about the disease and prevention, but poor knowledge about hemodialysis. Regarding the risk factors in the elderly investigated, increased are highlighted and statistical significance of waist circumference (p=0.049), smoking (p=0.022) and alcohol consumption (p=0.013). Conclusion: relationships between risk factors as smoking, alcoholism, increased abdominal circumference, and the knowledge of the elderly about chronic kidney disease were identified.